Problem based learning model on higher order thinking skills and self regulation of high school students - Listyono, Listyono; Rofi’ah , Ndzani Latifatur; Hendrika , Tasya Putri (Universitas Ahmad Dahlan, 2025)
21st century students are required to have critical thinking and problem solving skills, creativity and innovation, communication, collaboration to train students to have social skills and global insight. In addition, self-direction (crom), global connections, local connections and the use of technology as a learning tool support Higher Order Thinking Skills. The application of appropriate learning models can support the achievement of these skills. The purpose of this research is to analyze the effect of Problem Based Learning model on the ability of Higher Order Thinking Skills and analyze the effect of Problem Based Learning model on Self Regulation. The research method used quasi experimental with nonequivalent control group design. The sampling technique used was purposive sampling. The instruments used were interviews, test questions, Self Regulation questionnaire and documentation. Hypothesis testing using Anacova test. The results showed a difference in Higher Order Thinking Skills on the application of the Problem Based Learning model with a significance value of 0,000<0,05, indicating the Problem Based Learning learning model affects Higher Order Thinking Skills. There is a difference in Self Regulation in the application of the Problem Based Learning learning model with a significance value of 0,000<0,05.